1995
DOI: 10.1002/job.4030160507
|View full text |Cite
|
Sign up to set email alerts
|

Individual and group determinants of employee absenteeism: Test of a causal model

Abstract: This study examined whether an employee's level of absenteeism was affected by age, organizational tenure, perceptions of interactional justice, affective and continuance commitment, and the perceived absence norm in the employees' work unit or department. One hundred and sixty‐six nursing and food services employees in a mid‐size chronic care hospital provided attitudinal and perceptual data on an employee survey. Absence data (absence frequency and total days absent) were collected during the 12‐month period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
4
11

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(163 citation statements)
references
References 59 publications
7
141
4
11
Order By: Relevance
“…The negative relationship could be explained by the fact that older workers usually take up higher responsibility at work and are more satisfied, appreciating greater benefits (see, for instance, Siu 2002). However, it is consistent with Hoque and Islam (2003), who found a non-significant relationship between age and absenteeism, with Gellatly (1995), who suggested that age is negatively related to absence, and with Hackett (1990), who suggested that the relationship is quite complex, implying that other factors play a role too.…”
Section: Discussion and Concluding Commentssupporting
confidence: 56%
“…The negative relationship could be explained by the fact that older workers usually take up higher responsibility at work and are more satisfied, appreciating greater benefits (see, for instance, Siu 2002). However, it is consistent with Hoque and Islam (2003), who found a non-significant relationship between age and absenteeism, with Gellatly (1995), who suggested that age is negatively related to absence, and with Hackett (1990), who suggested that the relationship is quite complex, implying that other factors play a role too.…”
Section: Discussion and Concluding Commentssupporting
confidence: 56%
“…Social influence theories hold that members of a work unit develop shared attitudes about their jobs and organization because they have opportunities for information exchange, share similar structural characteristics, and generally experience the same events (e.g., Rentsch, 1990;Rentsch & Steel, 2003;Ryan, Schmit, & Johnson, 1996;Salancik & Pfeffer, 1978;Schneider & Reichers, 1983). In addition, unit supervisors and managers are responsible for the implementation and interpretation of organizational policies, rules, and procedures, and thus may guide employees to respond to organizational events in similar ways (Gellatly, 1995;Rentsch & Steel, 2003). Situational and social influences tend to create relatively homogeneous attitudes within work units, including shared levels of job satisfaction and organizational commitment.…”
Section: Explaining Work-unit Absenteeismmentioning
confidence: 99%
“…Furthermore, high absenteeism rate is often mentioned as another disincentive for investing in the training of older workers (Warwick Report, 2006). The latter are perceived as more expensive than younger workers, due to "a perceived higher rate of absenteeism and sick leave" (Gellatly, 1995). This was confirmed by a recent research of who found that HR professional are more likely to train older workers with lower absents.…”
Section: Training Participation: the Case Of Older Workersmentioning
confidence: 71%